The Expression of IbMYB1 Is Essential to Maintain the Purple Color of Leaf and Storage Root in Sweet Potato [Ipomoea batatas (L.) Lam] - Zhang, Daowei; Tan, Yongjun; Dong, Fang; Zhang, Ya; Huang, Yanlan; Zhou, Yizhou; Zhao, ZhiJian; Yin, Qin; Xie, Xuehua; Gao, Xiewang; Zhang, Chaofan; Tu, Naimei (Frontiers in Plant Science, 2021)
IbMYB1 was one of the major anthocyanin biosynthesis regulatory genes that has been identified and utilized in purple-fleshed sweetpotato breeding. At least three members of this gene, IbMYB1-1, -2a, and -2b, have been reported. We found that IbMYB1-2a and -2b are not necessary for anthocyanin accumulation in a variety of cultivated species (hexaploid) with purple shoots or purplish rings/spots of flesh. Transcriptome and RT-qPCR analyses revealed that persistent and vigorous expression of IbMYB1 is essential to maintain the purple color of leaves and storage roots in this type of cultivated species, which did not contain IbMYB1-2 gene copies. Compare with IbbHLH2, IbMYB1 is an early response gene of anthocyanin biosynthesis in sweetpotato. However, it cannot exclude the possibility that other MYBs participate in the regulation of this gene network. Twenty-two MYB-like genes were identified from 156 MYBs to be highly positively (negative) correlated with the anthocyanin content in leaves or flesh. Even so, the IbMYB1 work in the most coordination with anthocyanin biosynthesis genes. Differences in flanking and coding sequences confirm that IbMYB2s, the highest homologous copies of IbMYB1, are not the members of IbMYB1. This phenomenon indicates that there may be more members of IbMYB1 in sweetpotato, and genetic complementation of these members is involved in the regulation of anthocyanin biosynthesis. The 3' flanking sequence of IbMYB1-1 is homologous to the retrotransposon sequence of TNT1-94. Transposon movement is involved in the formation of multiple copies of IbMYB1. This study provides critical insights into the expression patterns of IbMYB1, which are involved in the regulation of anthocyanin biosynthesis in the leaf and storage root. Notably, our study also emphasized the presence of a multicopy gene of IbMYB1 for genetic improvement.